MASALAH PELAYANAN PUBLIK BIDANG PENDIDIKAN DI ERA DIGITAL PERSPEKTIF KOMUNIKASI (STUDI KASUS DINAS PENDIDIKAN KOTA PADANG) - Ghina Novarisa; Muhammad Fadhil; Muhammad Fadhel (Jurnal Ranah Komunikasi, 2023)
Public services in general have problems in their service to the community, such as: are protracted delays in service, abuse of authority, irregularities in procedures, not providing services, asking for money for services, incompetence, taking sides, discrimination, conflict interests and others. Digitalization of education is one form of transformation of public services at education field. Viewed from a communication perspective, digitalization of education is a form of improvement public services from the media elements, which influence other communication elements such as communicators, message, communication and of course the effect. This research aims to describe communication problems in public servants digitalizing education. This research uses a descriptive qualitative approach,using interview techniques and non-participant observation as data collection techniques. The result. However, from a communication perspective, these problems can be broken down into communicator problems and communication. Communicators who have insufficient knowledge of school digitalization, a mindset that is slow to accept change. Meanwhile, from the communicator's perspective, there are problems of poor communication skills, unsupportive attitudes from communicants, Insufficient knowledge of the program and technology, values and culture that hinder the process the communication.